THE CATEGORY «POLITICAL BEHAVIOR» IN THE STRUCTURE OF THE POLITICAL CULTURE OF SOCIETY - Vyacheslav Aleksandrovich Berkovsky (Современная наука и инновации)
The Article is devoted to the analysis of political behavior as a fundamental component of political culture of society. The paper treats the question of the relationship of political culture the concept of political behavior, its place and role in the structure of political culture. Reveal the essential characteristics and interpretations of this socio-political phenomenon on the basis of a multiparadigmatic approach.